STUDI ZONASI VEGETASI MANGROVE MUARA DI DESA UMBELE KECAMATAN BUMI RAYA KABUPATEN MOROWALI SULAWESI TENGAH - Samsumarlin, Samsumarlin; Rachman, Imran; Toknok, Bau (Universitas Tadulako, 2015)
The size of mangrove forest located in Bumi Raya Sub District, Morowali, Central Sulawesi is estimated to be about 9.8 ha. Research aimed at observing the mangrove vegetation zonation along with environmental condition parameter was conducted and taking place in Umbele Village. Primary and secondary data were collected. Primary data covered aspects such as species and number of individuals along with various parameters including salinity, acidity, soil textures, dissolved sulphate, tides on every observation station. Secondary data were collected from literature studies both in university and public libraries. The results of the study shows that there are about 17 mangrove species within 10 families located as rear zone. Parameter found to influence the existence of the mangrove are muddy and sandy soil as well as debrised muddy soil with pH ranging from 36 to 7.8. Meanwhile, salinity was recorded to range from 1.1 to 2.90 with tidal fluctuation from (0-13) cm to (13-220) cm. Key Words : Zonation, Vegetation, Mangrove.